Estimated dengue force of infection and burden of primary infections among Indian children - Amit Bhavsar; Clarence C. Tam; Suneela Garg; Guru Rajesh Jammy; Anne-Frieda Taurel; Sher-Ney Chong; Joshua Nealon (BMC, 2019)
Abstract Background Comprehensive, age-stratified dengue surveillance data are unavailable from India and many more dengue cases occur than are reported. Additional information on dengue transmission dynamics can inform understanding of disease endemicity and infection risk. Methods Using age-stratified dengue IgG seroprevalence data from 2556 Indian children aged 5-10 years, we estimated annual force of infection (FOI) at each of 6 sites using a binomial regression model. We estimated the ages by which 50 and 70% of children were first infected; and predicted seroprevalence in children aged 1-10 years assuming constant force-of-infection. Applying these infection rates to national census data, we then calculated the number of primary dengue infections occurring, annually, in Indian children. Results Annual force-of-infection at all sites combined was 11.9% (95% CI 8.8-16.2), varying across sites from 3.5% (95% CI 2.8-4.4) to 21.2% (95% CI 18.4-24.5). Overall, 50 and 70% of children were infected by 5.8 (95% CI 4.3-7.9) and 10.1 (95% CI 7.4-13.7) years respectively. In all sites except Kalyani, > 70% of children had been infected before their 11th birthday, and goodness-of-fit statistics indicated a relatively constant force-of-infection over time except at two sites (Wardha and Hyderabad). Nationwide, we estimated 17,013,527 children (95% CI: 14,518,438- 19,218,733), equivalent to 6.5% of children aged < 11 years, experience their first infection annually. Conclusions Dengue force-of-infection in India is comparable to other highly endemic countries. Significant variation across sites exists, likely reflecting local epidemiological variation. The number of annual primary infections is indicative of a significant, under-reported burden of secondary infections and symptomatic episodes. Trial registration Registered retrospectively with clinicaltrials.gov (NCT01477671; 18/11/2011) and clinical trials registry of India (ctri.nic.in; CTRI/2011/12/002243; 15/12/2011). Date of enrollment of 1st subject: 22/9/2011.